Estudo do comportamento dielétrico de equipamentos de manobra em média tensão através de software baseado no método dos elementos finitos - Sá, Erick Silva de (2019)
This work proposes the analysis of the dielectric behavior and the modeling of the ionization and air deionization phenomena in medium voltage protection / maneuvering switches - via electric field mapping. For this, numerical algorithms and software simulations based on the finite element method were used, particularly considering switch disconnectors, and fuse switches against standardized and non-standardized atmospheric discharges. From this analysis, critical regions with the highest probability of failure were mapped and geometric and / or functional modifications were made in the structure of these devices. These modifications minimized the high concentrations of electric field around the geometry of the equipment, and identified the possible voltage values that would cause the rupture of the dielectric medium of these equipment through the modeling of the air deionization/ionization phenomena.